Cultural Study and Cultural Paradok on Entrepreneurship Behavior of The Minang Community - Ibrahim Ibrahim (Journal of Social Science, 2022)
History records and the current reality has explained that the Minang people are an ethnic group known as the merchant tribe (entrepreneurs). His actions in trade from time to time have been recognized and his spread not only reaches his tribal areas but also extends to all parts of Indonesia and abroad. There are many amazing inspirational stories starting from the development of bilateral cooperation capabilities and the distribution of national ideologies through entrepreneurial activities. However, with all the potential and achievements achieved through entrepreneurship activities, it turns out that this profession is allegedly something that is not very coveted today by the Minang community. Entrepreneurship seems to be identified only for certain groups or qualifications of society and not for other communities. The entrepreneurial profession, which was originally something that was respected not only because of its ability to accumulate wealth but also its social effects, has become less "authoritative and elegant" in this day and age. It is necessary to study what phenomenon actually pervades the Minang community, where cultural wisdom upholds the entrepreneurship profession but the behavior of the people is indicated to be in the opposite direction.